Kefir induces cell-cycle arrest and apoptosis in HTLV-1-negative malignant T-lymphocytes - Rizk, Sandra (2011)
Background: Adult lymphoblastic leukemia (ALL) is a malignancy that occurs in white blood cells. The overall cure rate in children is 85%, whereas it is only 40% in adults. Kefir is an important probiotic that contains many bioactive ingredients, which give it unique health benefits. It has been shown to control several cellular types of cancer. Purpose: The present study investigates the effect of a cell-free fraction of kefir on CEM and Jurkat cells, which are human T-lymphotropic virus type I (HTLV-1)-negative malignant T-lymphocytes. Methods: Cells were incubated with different kefir concentrations. The cytotoxicity of the compound was evaluated by determining the percentage viability of cells. The effect of all the noncytotoxic concentrations of kefir on the proliferation of CEM and Jurkat cells was then assessed. The levels of transforming growth factor-alpha (TGF-α), transforming growth factor- beta1 (TGF-β1), matrix metalloproteinase-2 (MMP-2), and MMP-9 mRNA upon kefir treatment were then analyzed using reverse transcriptase polymerase chain reaction (RT-PCR). Finally, the growth inhibitory effects of kefir on cell-cycle progression/apoptosis were assessed by Cell Death Detection (ELISA) and flow cytometry. Results: The maximum cytotoxicity recorded after 48-hours treatment with 80 μg/μL kefir was only 42% and 39% in CEM and Jurkat cells, respectively. The percent reduction in proliferation was very significant, and was dose-, and time-dependent. In both cell lines, kefir exhibited its antiproliferative effect by downregulating TGF-α and upregulating TGF-β1 mRNA expression. Upon kefir treatment, a marked increase in cell-cycle distribution was noted in the preG1 phase of CEM and Jurkat cells, indicating the proapoptotic effect of kefir, which was further confirmed by Cell Death Detection ELISA. However, kefir did not affect the mRNA expression of metalloproteinases needed for the invasion of leukemic cell lines. Conclusion: In conclusion, kefir is effective in inhibiting proliferation and inducing apoptosis of HTLV-1-negative malignant T-lymphocytes. Therefore, further in vivo investigation is highly recommended.